Idiomatic use in the speech of students who have finished the advanced intensive english courses in the Foreign Language Department - Chávez Luna, Ana Cecilia; Serrano Sánchez, Verónica Argelia; Vaquerano Cañada, William Ernesto (2024)
This research is based on the fact that students who have finished the Advanced English courses have some problems to express their ideas at the moment of speaking about topics which are not related with English teaching. As a result, it shows a level which isn’t advanced or the required level to develop in everyday life situations. According to the American Council on the Teaching of Foreign Language (ACTFL) Proficiency Guidelines, a person who is in the advanced level must be able to speak the language with structural accuracy and proper vocabulary to participate effectively in most formal and informal conversations, and even though students from the Foreign Language Department (FLD) are supposed to accomplish that level when they finish the Intensive Courses; during some personal interviews it has been observed that idiomatic expressions are not used enough, or in some cases they are not understood by the students. As a result, most of them do not fit in that level since they are deficient in the use of idiomatic expressions, which is very important in speech. The objective of this research is to establish the causes that lead the students from the FLD to have this deficiency.